1997
DOI: 10.1161/01.cir.96.6.1999
|View full text |Cite
|
Sign up to set email alerts
|

Insights From Three-Dimensional Echocardiography Into the Mechanism of Functional Mitral Regurgitation

Abstract: LV dysfunction without dilatation fails to produce important MR. Functional MR relates strongly to changes in the 3D geometry of the mitral valve attachments at the PM and annular levels, with practical implications for approaches that would restore a more favorable configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
377
1
19

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 534 publications
(417 citation statements)
references
References 56 publications
16
377
1
19
Order By: Relevance
“…A introdução da ecocardiografia foi oportuna e acrescentou dados importantes para a compree n s ã o d o s m e c a n i s m o s r e s p o n s á v e i s p e l a regurgitação valvar mitral observada na CMD, mas, de outra forma, limitou os estudos anatômicos, tão necessários para dar suporte às observações obtidas (4,5) .…”
Section: Introductionunclassified
“…A introdução da ecocardiografia foi oportuna e acrescentou dados importantes para a compree n s ã o d o s m e c a n i s m o s r e s p o n s á v e i s p e l a regurgitação valvar mitral observada na CMD, mas, de outra forma, limitou os estudos anatômicos, tão necessários para dar suporte às observações obtidas (4,5) .…”
Section: Introductionunclassified
“…For example, the contractility of the concerned PM decreases in the setting of an acute MI that affects the blood supply to the PM. In addition, MR is caused by coaptation failure of the mitral leaflets due to spatial imbalances in the mitral complex, including the PMs, in patients with a dilated heart or regional asynergy of the LV wall [2,3]. One study [8] recently proposed that PMs do not attach directly to the solid heart wall.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Otsuji et al [3] demonstrated that the main cause of ischemic MR is augmented leaflet tethering by outward displacement of the PM in patients with LV remodeling. Their results are consistent with a previous transesophageal 2-dimensional echocardiographic study [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In this current issue of the European Heart JournalCardiovascular Imaging, members of these groups, using a related technology, have employed ultrasound to treat as well as to image the heart 3 in mitral regurgitation (MR) secondary to myocardial infarction (MI) that causes mitral valve (MV) leaflet tethering mediated by chordae to the displaced papillary muscles (PMs). 4 This is a condition for which a strong need is perceived for improved approaches. 5 Although there is evidence for adaptive MV growth in secondary MR, 6,7 this extra leaflet tissue is often insufficient to compensate adequately for mitral annular (MA) enlargement and chordal tethering.…”
mentioning
confidence: 99%